The flame spread performance over discrete wooden chips varying wood species. (1st March 2023) - Wang, Huiqiang; Wang, Zhengyang; Wen, Lijun; Meng, Hongping; Wang, Wei; Huang, Xiaobing
Highlights: The effect of wood species on the flame spread performance was studied by multiple factors. A new empirical model to predict TBD was modified according to the moisture content of wood. The relationship between the wood physical properties and fire spread performance was analyzed. Abstract: Wood is believed to be a good material used for the thermal insulation of building. However, the wood species vary greatly from region to region in China. With an aim to have a deep understanding of the influence of wood species on upward flame spread performance, a series of tests were conducted to obtain the profile of mass loss rate (MLR), flame spread rate (FSR), total burning duration (TBD), and the maximum flame characteristic length (MFL) by using a traditional flame spreading measurement facility. During the tests, beech wood, fir wood, pine wood, camphor wood and elm wood were selected as typical samples. The results and discussion indicate that wood species imposed a strong effect on the flame spread performance. The total burning duration (TBD) of wood with high moisture content and high solidity is significantly higher than that of other types of wood. Softwoods with higher lignin content and lower hemicellulose can increase the FSR to a certain extent. Moreover, the moisture content of wood is found to have a big impact on the MLR. Based on the discussion of different parameters, it can be judged that the fire safety of the historic wooden buildings made of Fir wood is more excellent than others.